A new encryption system for IoT devices using embedded key cryptosystem. (14th November 2022) - Masadeh, Shadi R.
IoT constrained devices have special phenomena of constrained resources such as power source, memory and processing power. Besides, it is vital to achieve an acceptable level of security and privacy while preserving the IoT device resources. In this paper, a new cryptographic algorithm is developed that would be suitable for securing IoT devices using embedded key cryptosystem. The encryption/decryption processes are achieved by segmenting the message into blocks of certain length. Each block is encrypted/decrypted using a key that is generated according to the segment itself, i.e., the keys are embedded into the blocks. The algorithm adopts two tables: one for the intended character set and the other for the key elements generation. The secrecy of these tables is responsible for securing the key strength. Experimental implementation proves the algorithm feasibility and strength against hackers and intruders.